Effects of Physical Education Frequency, Activity Intensity and Activity Type on Middle School Students’ Cognitive Performance - Li, Xiao; Arifani, Yudhi (Prosiding University Research Colloquium, 2025)
This study aimed to examine how the frequency of physical education (PE) classes, the intensity of physical activity, and different types of exercises influence middle school students’ cognitive performance. Understanding these relationships can help optimize PE programs to enhance students’ attention, memory, and executive function. A quasi-experimental design was employed, involving 300 middle school students aged 11 to 14 years, who were divided into groups based on PE class frequency (one, two, or three sessions per week), activity intensity (low, moderate, high), and activity type (aerobic, skill-based, mind-body). Cognitive performance was assessed using the standardized test after a 12-week intervention. Physical activity intensity was measured using wearable fitness trackers, and engagement levels were monitored through teacher observations and student self-reports. The findings revealed that students attending PE classes more frequently and engaging in moderate to high-intensity activities showed significantly improved cognitive performance. Aerobic exercises were linked to enhanced attention and memory, while skill-based activities improved executive function. Mind-body exercises provided moderate benefits, particularly in stress reduction and focus. The study highlights the positive impact of structured and frequent PE sessions on cognitive development. Schools should incorporate various physical activities with sufficient intensity to maximize students’ cognitive and academic performance.